Challenges of Using Applied Behavior Analysis (ABA) by Saudi Special Education Teachers to Improve the Social Skills of Students with Autism - Salman Almughyiri (SAGE Open)
In the 21st century, ABA has gained prominence in educational research in Western countries because of the evidence supporting its efficacy. However, the volume of research and the usage of ABA among teachers of students with ASD in the Kingdom of Saudi Arabia (KSA) remains considerably low despite its popularity in other regions globally. Aims : This study aimed to explore the perspectives and experiences of teachers of students with autism in Riyadh and Jeddah related to the use of applied behavior analysis (ABA) to improve social skills. A qualitative method was used to analyze phenomena under inquiry from two different data points: surveys ( n  = 51) and interviews ( n  = 6). Results : The findings of this study revealed that some of the main factors affecting how teachers view and utilize evidence-based practice (EBP) in their scope of practice are refresher training, skills, knowledge, peer support, and institutional policies. Discussion and conclusion were discussed.